CO2 mineralized cementing material based on steel slag-mineral slag-fly ash multi-element solid waste and preparation method of CO2 mineralized cementing material

By using multiple solid waste materials such as steel slag, slag and fly ash in fly ash gelling materials, combined with the excitants of aluminum sulfate, calcium aluminate and sodium hydroxide, the low initial strength of fly ash gelling materials is solved. The problem is that high mechanical strength and low cost resource utilization have been achieved.

CN119285317AInactive Publication Date: 2025-01-10ZHEJIANG UNIV

Patent Information

Application Number
CN202411400569.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The early strength of fly ash gelling materials is low, limiting their application in building materials. The existing research formulas are similar and have failed to effectively stimulate the activity of fly ash.

Method used

Using multi-purpose solid waste materials such as steel slag, slag and fly ash, combined with a composite exciter of aluminum sulfate, calcium aluminate and sodium hydroxide, it is prepared by alkali excitation and aluminate excitation, combined with crosslinking agent and defoaming agent. High mechanical strength C02 mineralized gelling material.

Benefits of technology

It significantly improves the early strength of gelled materials, has simple production process and low cost, realizes low-carbon and environmentally friendly resource utilization, and reduces production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a CO2 mineralized cementing material based on steel slag-mineral slag-fly ash multi-element solid waste and a preparation method, and relates to the technical field of building materials. The CO2 mineralized cementing material based on the steel slag-slag-fly ash multi-element solid waste is prepared from the following raw materials in parts by mass: 10 to 15 parts of steel slag, 30 to 40 parts of slag, 50 to 60 parts of slag fly ash, 5 to 20 parts of gypsum, 1 to 5 parts of clinker, 1 to 5 parts of cement, 5 to 20 parts of exciting agent, 4 to 6 parts of cross-linking agent composition, 0.1 to 0.5 part of alkaline water and 0.1 to 0.5 part of defoaming agent. According to the invention, the steel slag, the furnace slag and the furnace slag fly ash are excited by adopting a composite exciting agent of aluminum sulfate, calcium aluminate and sodium hydroxide, the problem of early strength is successfully solved through alkali excitation and aluminate excitation, the proportion of the exciting agent is reasonably configured, the effect of the exciting agent is exerted to the maximum extent, and the mechanical strength of the CO2 mineralized cementing material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and specifically to a C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste and a preparation method thereof. Background Art

[0002] Fly ash is the fine ash collected from the flue gas after coal combustion. It is the main solid waste discharged by coal-fired power plants. The main oxide components of fly ash from thermal power plants in my country are: SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. With the development of the power industry, the amount of fly ash discharged from coal-fired power plants has increased year by year, becoming one of the largest industrial waste residues in my country. If a large amount of fly ash is not treated, it will generate dust and pollute the atmosphere; if it is discharged into the water system, it will cause river siltation, and the toxic chemicals in it will also cause harm to humans and organisms.

[0003] However, fly ash can also be utilized as a resource, such as preparing cementitious materials. Currently, there are many studies on fly ash cementitious materials, and the basic formulas are relatively similar. The later strength of fly ash cementitious materials is relatively high, generally greater than 42.5Mpa. Although fly ash itself has certain activity, its early stimulation effect is limited, resulting in lower early strength.

[0004] Therefore, those skilled in the art provide a C02 mineralized cementitious material and preparation method based on steel slag-slag-fly ash multi-solid waste to solve the problems raised in the above background technology. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the shortcomings of the prior art, the present invention provides a C02 mineralized cementitious material and a preparation method based on steel slag-slag-fly ash multi-solid waste, which solves the problem that fly ash can also be utilized as a resource, such as preparing cementitious materials. Currently, there are many studies on fly ash cementitious materials, and the basic formulas are relatively similar. The later strength of fly ash cementitious materials is relatively high, generally greater than 42.5Mpa. Although fly ash itself has certain activity, its early stimulation effect is limited, resulting in the problem of low early strength.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A CO2 mineralized cementitious material based on steel slag-blast furnace slag-fly ash multi-solid waste, comprising the following raw materials in parts by weight: 10-15 parts of steel slag, 30-40 parts of blast furnace slag, 50-60 parts of slag fly ash, 5-20 parts of gypsum, 1-5 parts of clinker, 1-5 parts of cement, 5-20 parts of activator, 4-6 parts of cross-linking agent composition, 0.1-0.5 parts of alkaline water agent, and 0.1-0.5 parts of defoaming agent.

[0010] Preferably, the raw material composition includes the following parts by mass: 12 parts of steel slag, 35 parts of slag, 55 parts of slag fly ash, 15 parts of gypsum, 3 parts of clinker, 3 parts of cement, 12 parts of chemical activator, 5 parts of cross-linking agent composition, 0.3 parts of alkaline water agent, and 0.2 parts of defoaming agent.

[0011] Preferably, the raw material composition includes the following parts by mass: 10 parts of steel slag, 30 parts of slag, 50 parts of slag fly ash, 5 parts of gypsum, 1 part of clinker, 1 part of cement, 5 parts of chemical activator, 4 parts of cross-linking agent composition, 0.1 part of alkaline water agent, and 0.1 part of defoaming agent.

[0012] Preferably, the raw material composition includes the following parts by mass: 15 parts of steel slag, 40 parts of slag, 60 parts of slag fly ash, 20 parts of gypsum, 5 parts of clinker, 5 parts of cement, 20 parts of chemical activator, 6 parts of cross-linking agent composition, 0.5 parts of alkaline water agent, and 0.5 parts of defoaming agent.

[0013] Preferably, the steel slag is one of electric furnace steel slag, converter steel slag and open-hearth steel slag, and the slag is iron-making blast furnace slag powder.

[0014] Preferably, the gypsum is one of desulfurized gypsum, phosphogypsum and anhydrite.

[0015] Preferably, the activator comprises aluminum sulfate, calcium aluminate and sodium hydroxide, and the mass ratio of the aluminum sulfate, calcium aluminate and sodium hydroxide is: (8-9): 1: (3-5).

[0016] Preferably, the crosslinker composition comprises DCP, LLDPE and silane in a weight ratio of 1:40:6.

[0017] Preferably, a method for preparing a C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste comprises the following steps:

[0018] Step S1. After the steel slag, slag and slag pulverized coal are ball-milled respectively, they are weighed and mixed in proportion to obtain a mixture;

[0019] Step S2. Gypsum, clinker, cement and activator are weighed in proportion and ground together to form auxiliary powder for activating the activity of steel slag, slag and slag fly ash;

[0020] Step S3. Then, the mixture obtained in the above step and the auxiliary material powder are added into a mixer for mixing to obtain a premix;

[0021] Step S4. dissolving the crosslinking agent composition, alkaline water agent and defoaming agent in a certain amount of water, and then adding them to the above premix, stirring evenly to obtain the C02 mineralized gelling material.

[0022] Step S5: curing the prepared gel material for 15-28 days.

[0023] Preferably, the fineness of the CO2 mineralized gelling material is greater than 3700 cm 2 / g.

[0024] (III) Beneficial effects

[0025] The present invention provides a C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste and a preparation method thereof. It has the following beneficial effects:

[0026] 1. The present invention provides a C02 mineralized cementitious material and preparation method based on steel slag-slag-fly ash multi-solid waste. The composite activator of aluminum sulfate, calcium aluminate and sodium hydroxide is used to activate steel slag, furnace slag and furnace slag fly ash. The early strength problem is successfully solved through alkali activation and aluminate activation. The ratio of the activator is reasonably configured to maximize the effect of the activator and improve the mechanical strength of the C02 mineralized cementitious material.

[0027] 2. The present invention provides a C02 mineralized cementitious material and preparation method based on steel slag-slag-fly ash multi-solid waste. The production process is simple and can be summarized as "two grindings and one mixing", namely slag grinding, auxiliary material grinding and finished product mixing. The production cost is low, low-carbon and environmentally friendly, and a lower mixing ratio of cementitious materials and tailings can be achieved, further reducing production costs. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Embodiment 1:

[0030] An embodiment of the present invention provides a C02 mineralized cementitious material based on steel slag-blast furnace slag-fly ash multi-solid waste, comprising the following raw material compositions in parts by mass: 12 parts of steel slag, 35 parts of blast furnace slag, 55 parts of slag fly ash, 15 parts of gypsum, 3 parts of clinker, 3 parts of cement, 12 parts of chemical activator, 5 parts of cross-linking agent composition, 0.3 parts of alkaline water agent, and 0.2 parts of defoaming agent.

[0031] The steel slag is electric furnace slag, the slag is iron-making blast furnace slag powder, the gypsum is desulfurized gypsum, the activator includes aluminum sulfate, calcium aluminate and sodium hydroxide, the mass ratio of aluminum sulfate, calcium aluminate and sodium hydroxide is 8:1:5, and the cross-linking agent composition includes DCP, LLDPE and silane, and the weight ratio is 1:40:6.

[0032] The preparation method of the CO2 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste comprises the following steps:

[0033] Step S1. After the steel slag, slag and slag pulverized coal are ball-milled respectively, they are weighed and mixed in proportion to obtain a mixture;

[0034] Step S2. Gypsum, clinker, cement and activator are weighed in proportion and ground together to form auxiliary powder for activating the activity of steel slag, slag and slag fly ash;

[0035] Step S3. Then, the mixture obtained in the above step and the auxiliary material powder are added into a mixer for mixing to obtain a premix;

[0036] Step S4. dissolving the crosslinking agent composition, alkaline water agent and defoaming agent in a certain amount of water, then adding them to the above premix, stirring evenly to obtain the C02 mineralized gelling material.

[0037] Step S5: curing the prepared gel material for 20 days.

[0038] Embodiment 2:

[0039] An embodiment of the present invention provides a C02 mineralized cementitious material based on steel slag-blast furnace slag-fly ash multi-solid waste, comprising the following raw material compositions in parts by mass: 10 parts of steel slag, 30 parts of blast furnace slag, 50 parts of slag fly ash, 5 parts of gypsum, 1 part of clinker, 1 part of cement, 5 parts of chemical activator, 4 parts of cross-linking agent composition, 0.1 part of alkaline water agent, and 0.1 part of defoaming agent.

[0040] The steel slag is electric furnace slag, the slag is iron-making blast furnace slag powder, the gypsum is desulfurized gypsum, the activator includes aluminum sulfate, calcium aluminate and sodium hydroxide, the mass ratio of aluminum sulfate, calcium aluminate and sodium hydroxide is 8:1:5, and the cross-linking agent composition includes DCP, LLDPE and silane, and the weight ratio is 1:40:6.

[0041] The preparation method of the CO2 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste comprises the following steps:

[0042] Step S1. After the steel slag, slag and slag pulverized coal are ball-milled respectively, they are weighed and mixed in proportion to obtain a mixture;

[0043] Step S2. Gypsum, clinker, cement and activator are weighed in proportion and ground together to form auxiliary powder for activating the activity of steel slag, slag and slag fly ash;

[0044] Step S3. Then, the mixture obtained in the above step and the auxiliary material powder are added into a mixer for mixing to obtain a premix;

[0045] Step S4. dissolving the crosslinking agent composition, alkaline water agent and defoaming agent in a certain amount of water, and then adding them to the above premix, stirring evenly to obtain the C02 mineralized gelling material.

[0046] Step S5: curing the prepared gel material for 20 days.

[0047] Embodiment 3:

[0048] An embodiment of the present invention provides a C02 mineralized cementitious material based on steel slag-blast furnace slag-fly ash multi-solid waste, comprising the following raw material compositions in parts by mass: 15 parts of steel slag, 40 parts of blast furnace slag, 60 parts of slag fly ash, 20 parts of gypsum, 5 parts of clinker, 5 parts of cement, 20 parts of chemical activator, 6 parts of cross-linking agent composition, 0.5 parts of alkaline water agent, and 0.5 parts of defoaming agent.

[0049] The steel slag is electric furnace slag, the slag is iron-making blast furnace slag powder, the gypsum is desulfurized gypsum, the activator includes aluminum sulfate, calcium aluminate and sodium hydroxide, the mass ratio of aluminum sulfate, calcium aluminate and sodium hydroxide is 8:1:5, and the cross-linking agent composition includes DCP, LLDPE and silane, and the weight ratio is 1:40:6.

[0050] The preparation method of the CO2 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste comprises the following steps:

[0051] Step S1. After the steel slag, slag and slag pulverized coal are ball-milled respectively, they are weighed and mixed in proportion to obtain a mixture;

[0052] Step S2. Gypsum, clinker, cement and activator are weighed in proportion and ground together to form auxiliary powder for activating the activity of steel slag, slag and slag fly ash;

[0053] Step S3. Then, the mixture obtained in the above step and the auxiliary material powder are added into a mixer for mixing to obtain a premix;

[0054] Step S4. dissolving the crosslinking agent composition, alkaline water agent and defoaming agent in a certain amount of water, and then adding them to the above premix, stirring evenly to obtain the C02 mineralized gelling material.

[0055] Step S5: curing the prepared gel material for 20 days.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste, characterized in that: The raw material composition includes the following parts by weight: 10-15 parts of steel slag, 30-40 parts of slag, 50-60 parts of slag fly ash, 5-20 parts of gypsum, 1-5 parts of clinker, 1-5 parts of cement, 5-20 parts of activator, 4-6 parts of crosslinking agent composition, 0.1-0.5 parts of alkaline water agent, and 0.1-0.5 parts of defoaming agent.

2. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1 is characterized in that: The invention comprises the following raw materials in parts by weight: 12 parts of steel slag, 35 parts of slag, 55 parts of slag fly ash, 15 parts of gypsum, 3 parts of clinker, 3 parts of cement, 12 parts of chemical activator, 5 parts of crosslinking agent composition, 0.3 parts of alkaline water agent and 0.2 parts of defoaming agent.

3. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1, characterized in that: The raw material composition includes the following parts by weight: 10 parts of steel slag, 30 parts of slag, 50 parts of slag fly ash, 5 parts of gypsum, 1 part of clinker, 1 part of cement, 5 parts of chemical activator, 4 parts of cross-linking agent composition, 0.1 part of alkaline water agent, and 0.1 part of defoaming agent.

4. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 15 parts of steel slag, 40 parts of slag, 60 parts of slag fly ash, 20 parts of gypsum, 5 parts of clinker, 5 parts of cement, 20 parts of chemical activator, 6 parts of cross-linking agent composition, 0.5 parts of alkaline water agent and 0.5 parts of defoaming agent.

5. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1, characterized in that: The steel slag is one of electric furnace steel slag, converter steel slag and open-hearth steel slag, and the slag is iron-making blast furnace slag powder.

6. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1, characterized in that: The gypsum is one of desulfurized gypsum, phosphogypsum and anhydrite.

7. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1, characterized in that: The activator comprises aluminum sulfate, calcium aluminate and sodium hydroxide, and the mass ratio of the aluminum sulfate, calcium aluminate and sodium hydroxide is: (8-9): 1: (3-5).

8. The C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 1, characterized in that: The crosslinking agent composition comprises DCP, LLDPE and silane, and the weight ratio is 1:40:

6.

9. The method for preparing a C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1. After the steel slag, slag and slag pulverized coal are ball-milled respectively, they are weighed and mixed in proportion to obtain a mixture; Step S2. Gypsum, clinker, cement and activator are weighed in proportion and ground together to form auxiliary powder for activating the activity of steel slag, slag and slag fly ash; Step S3. Then, the mixture obtained in the above step and the auxiliary material powder are added into a mixer for mixing to obtain a premix; Step S4. dissolving the crosslinking agent composition, the alkaline water agent and the defoaming agent in a certain amount of water, and then adding them to the premix, stirring evenly to obtain the C02 mineralized gelling material; Step S5: curing the prepared gel material for 15-28 days.

10. The method for preparing a C02 mineralized cementitious material based on steel slag-slag-fly ash multi-solid waste according to claim 9, wherein the fineness of the C02 mineralized cementitious material is greater than 3700 cm 2 / g.

Citation Information

Patent Citations

  • Silane crosslinked LLDPE material as well as preparation method and application thereof

    CN113698692A

  • Fly ash cementing material

    CN114455899A

  • Environment-friendly cementing material and preparation method thereof

    CN116874240A

Cited By

  • Mineralized cementing material and preparation method thereof

    CN120097650A

  • A mineralized cementitious material and its preparation method

    CN120097650B

  • Preparation method and application of composite solid waste-based cementing material

    CN122010438A